Effects of soil coverage upon the structuring and functioning of soil microbiome - Bresciani, Luana (2021)
The exponential increase of world population has raised the demand for energy and food resources. In order to achieve it, alternative practices are required to improve agricultural production using fewer natural resources. It is essential, among other factors, to achieve a better soil quality for sustainable production, which turns fundamental to keep soil permanently covered by crop residues or cover crops. Soil coverage acts as a physical barrier to soil losses and increases soil organic matter, enhancing the aggregate structure and nutritional availability. However, little is known about soil coverage\'s influence on the microbial community. Here, we studied the effect of soil coverage on bacterial communities in coffee and sugarcane plantations. Coffee was evaluated comparing conventional and intercropping systems, while sugarcane was studied in four levels of straw maintained in soil surface [total remove (TR), high remove (HR), low remove (LR), and no remove (NR)]. We assessed bacterial community from 0 - 15 cm, divided into four layers in coffee, and 0 - 20 cm, along with five layers in sugarcane crop. We evaluated β-glucosidase and acid-phosphatase activities, biological nitrogen fixation and phosphorus solubilization functional genes abundance (nifH and phoD, respectively), and bacterial community by 16S rRNA sequencing. Further, we performed network co-occurrence analysis and topological parameters to evaluate bacterial assembly and interactions. Our results propose that soil coverage provides a more stable environment for bacterial communities\' development, functioning, and structuring. Our findings indicate that bacterial communities interplay with soil coverage, and its outcomes may boost bacterial benefits for crop performance. The resulting communities observed in both systems under soil coverage can protect the plant from pathogen invasion and benefit the plant by nutritional supply and efficient use of soil resources. Overall, this study contributed to better understand bacterial communities in agricultural soils, which is essential to future design better practices for a more sustainable agricultural system.